2019
DOI: 10.3390/en12091655
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Trade, Urbanization and Environmental Degradation Nexus in Sri Lanka: Bounds Testing Approach

Abstract: This study examines the nexus between energy, trade, urbanization and environmental degradation in Sri Lanka. The time series data has been checked for unit root problem along with unknown structural break. The bounds testing approach confirms the long-term relationship among carbon emissions, energy consumption, income, trade openness, and urbanization in the presence of structural break. The results of the study do not confirm the presence of the EKC (Environmental Kuznets Curve) hypothesis in Sri Lanka. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 51 publications
5
29
0
Order By: Relevance
“…ey further confirm the bidirectional causal relationship between carbon emission, energy consumption, and economic growth in short run. Likewise, Gasimli, Gamage, Shihadeh, Rajapakshe, and Shafiq [18] studied the association between trade, energy, urbanization, and environmental degradation where the findings of their study indicate that there exists a long-term association between these variables. ey further stipulate that energy consumption will cause short-term and long-term carbon emissions.…”
Section: Trade Openness and Carbon Emissionmentioning
confidence: 99%
“…ey further confirm the bidirectional causal relationship between carbon emission, energy consumption, and economic growth in short run. Likewise, Gasimli, Gamage, Shihadeh, Rajapakshe, and Shafiq [18] studied the association between trade, energy, urbanization, and environmental degradation where the findings of their study indicate that there exists a long-term association between these variables. ey further stipulate that energy consumption will cause short-term and long-term carbon emissions.…”
Section: Trade Openness and Carbon Emissionmentioning
confidence: 99%
“…On the other hand, negative arguments are raised by some researchers due to the fact that increased exports lead to increased industrial production activities, which ultimately increase CO 2 emissions and, hence, damage environmental quality [51]. Empirically, Jebli, Youssef [52], Balsalobre-Lorente, Shahbaz [37], Gasimli, Gamage [53], Mahmood, Maalel [54], Murad and Mazumder [55], Tiwari, Shahbaz [13], and Halicioglu [56], found detrimental effects of trade on the environment in 22 Central and South American countries, 5 EU countries, as well as Sri Lanka, Tunisia, Malaysia, India, and Turkey. In contrast, Khan, Ali [57] demonstrated that exports decreased and imports increased consumption-based carbon emissions in nine oil-exporting countries.…”
Section: Co 2 Emissions-trade/exports Nexusmentioning
confidence: 99%
“…In the next 25 years Africa's energy use is expected to be influenced by a fast growing population and high economic activities and this will in turn affect world energy markets (International energy outlook, 2018). Furthermore, urbanization has been identified as another important contributor to economic growth (Gasimli et al, 2019). Urbanization-driven population increase, industrialization (Uttara et al, 2012), income and overexploitation of natural resources are associated with deterioration in significant environmental indicators pertaining to, inter alia, air, soil, water and forest quality.…”
Section: Introductionmentioning
confidence: 99%